Exploring the ecosystem of K-12 online learning: an empirical study of impact mechanisms in the post-pandemic era - Wang, Ping; Wang, Feiye; Li, Zhiyuan (Frontiers in Psychology, 2023)
With the normalization of the COVID-19 epidemic, online learning has gained prominence in the post-epidemic era. Gaining a comprehensive understanding of how online learning influences learning outcomes is essential for the success of large-scale online education initiatives. This study proposed a conceptual model based on an ecosystem theory to investigate the impact of K-12 online learning on academic achievement. A survey was conducted among 1,625 K-12 school students in Shenzhen, China, utilizing Structural Equation Modeling (SEM) for data analysis. The results indicate the following: (1) online learning engagement directly predicts academic achievement and mediates personal and environmental factors; (2) Family involvement and school support have similar impacts, with family involvement slightly stronger; (3) The Big Five Personality, especially conscientiousness, openness, and emotional stability, mediate the influence of family and school investment; and (4) School support affects academic achievement through online learning engagement, with emotional engagement being most significant. Our model illuminates the mediating role of online learning engagement, the impact of family involvement and school support, and the significance of Big Five Personality traits in K-12 online learning. This study contributes to the theoretical and practical understanding of the online learning ecosystem in the post-pandemic era, seldom explored in K-12 settings.